Dependence of maximal sniff generated mouth and transdiaphragmatic pressures on lung volume. Issue 5 (May 1990) - Wanke, T; Schenz, G; Zwick, H; Popp, W; Ritschka, L; Flicker, M
Abstract : The maximal sniff generated mouth and transdiaphragmatic pressures of six healthy volunteers (three women and three men) were measured at various lung volumes between residual volume and 95% of total lung capacity. At residual volume the mean (SD) maximum transdiaphragmatic pressure was 163 (18) cm H2O (1 cm H2O = 0.0981 kPa). With increasing lung volume the maximum pressures generated declined, so that at 95% of total lung capacity the mean pressure was 68 (15) cm H2O. Mouth pressures showed a similar relation to lung volume. At residual volume the mean maximum mouth pressure was 74 (8) cm H2O, compared with 38 (6) cm H2O at 95% of total lung capacity. The relation between pressure and lung volume was linear for measurements at lung volume levels between residual volume and 85% of total lung capacity; values at 95% of total lung capacity, however, were lower than predicted from the linear regression of the other points. The use of a second order polynomial regression showed a higher coefficient of determination in all cases (0.72 and 0.69 for transdiaphragmatic and mouth pressures on the basis of all pressure values for all subjects). Sniff generated mouth and transdiaphragmatic pressures show a predictable dependence on lung volume, supporting their use as measures of global inspiratory muscle power and diaphragm strength respectively.